Alterations in peripheral joint muscle force control in adults with musculoskeletal disease, injury, surgery, or arthroplasty: A systematic review and meta-analysis. (October 2022) - Pethick, Jamie; Clark, Nicholas C.; Liew, Bernard
Abstract: Purpose: To systematically review and analyse whether musculoskeletal conditions affect peripheral joint muscle force control (i.e. magnitude and/or complexity of force fluctuations). Methods: A literature search was conducted using MEDLINE, CINAHL and SPORTDiscus databases (from inception-8th April 2021) for studies involving: 1) participants with musculoskeletal disease, injury, surgery, or arthroplasty in the peripheral joints of the upper/lower limb; 2) comparison with an unaffected control group or unaffected contralateral limb; and 3) measures of the magnitude and/or complexity of force fluctuations during targeted isometric contractions. The methodological quality of studies was evaluated using a modified Downs and Black Quality Index. Studies were combined using the standardized mean difference (SMD) in a random-effects model. Results: 14 studies (investigating 694 participants) were included in the meta -analysis. There was a significant effect of musculoskeletal conditions on peripheral joint muscle force coefficient of variation (CV; SMD = 0.19 [95 % CI 0.06, 0.32]), whereby individuals with musculoskeletal conditions exhibited greater CV than controls. Subgroup analyses revealed that CV was only greater: 1) when comparison was made between symptomatic and asymptomatic individuals (rather than between affected and contralateral limbs; SMD = 0.22 [95 % CI 0.07, 0.38]); 2) for conditions of the knee (SMD = 0.29 [95 % CI 0.14, 0.44]); and 3) for ACL injury post-surgery (SMD = 0.56 [95 % CI 0.36, 0.75]). Conclusion: Musculoskeletal conditions result in an increase in peripheral joint muscle force CV, with this effect dependent on study design, peripheral joint, and surgical status. The greater force CV is indicative of decreased force steadiness and could have implications for long-term tissue health/day-to-day function.